Analisis Persebaran Artefak Visual Wayang Beber Klasik di Jawa: Interpretasi dan Kontekstualisasinya Terhadap Kronik Sejarah Jawa Era Mataram Islam - Bagus Permadi, Topan (Faculty of Arts and Design, Jakarta Institute of the Arts, 2026)
This article analyzes the results of mapping the distribution of classical wayang beber artifacts on the island of Java using a historical study approach. The analysis then proceeds with an effort at interpretation and an in-depth study of the knowledge contained both within and outside the artifacts based on data sources. The wayang beber artifacts analyzed consist of 6 sets of wayang beber artifacts in Pacitan, 8 sets of wayang beber artifacts in Wonosari, and 6 sets of wayang beber artifacts at the Netherlands Museum of Ethnology. By applying a descriptive qualitative research method elaborated through a historical study approach, this article summarizes the finding that the distribution of wayang beber artifacts in Java is part of the geopolitical conditions of the Islamic Mataram Kingdom. Furthermore, this article presents findings that the creation of classical wayang beber visual artifacts distributed across Java exhibits parallels or connections with contemporary events, consistent with analyses of the candrasekala calendar and radiocarbon dating results. The results of this study explain that the classical wayang beber artifacts that still exist today are part of the cultural history of Islamic Mataram in Java, and serve as works of art that implicitly encapsulate political events, history, and the legitimacy of a king all packaged within the romantic narrative of the Panji story cycle and visualized as scenes in wayang beber paintings.